2020
DOI: 10.1186/s12870-020-2278-9
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal application of various sulfonylurea and imidazolinone herbicides favors outcrossing and hybrid seed production in oilseed rape

Abstract: Background: Acetolactate synthase (ALS)-inhibiting herbicides from the chemical families of sulfonylureas and imidazolinones are used worldwide. However, drift or sprayer contamination from some sulfonylurea herbicides causes a high level of male sterility in cruciferous species, especially oilseed rape (OSR). In this paper, we evaluated the gametocidal effects of 27 ALS-inhibiting herbicides that were sprayed on OSR plants at the bolting stage. Results: OSR anther development was very sensitive to sublethal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In this study, the gametocidal effect of herbicides was tested on both fertile lines and unstable male sterile Polima lines (SU only). It has been shown that imidazolinone group herbicides have a gametocidal effect and can induce more than 90% male sterility when 750-1125 mg/ha imazethapyr and 400-800 mg/ha imazamox are applied [46]. The effect of imidazolinone group herbicides on increasing the purity of hybrid seeds when hybridized with Polima male sterile lines was not evaluated in this study.…”
Section: Improving Hybrid Seed Purity Using Imidazolinonesmentioning
confidence: 91%
See 4 more Smart Citations
“…In this study, the gametocidal effect of herbicides was tested on both fertile lines and unstable male sterile Polima lines (SU only). It has been shown that imidazolinone group herbicides have a gametocidal effect and can induce more than 90% male sterility when 750-1125 mg/ha imazethapyr and 400-800 mg/ha imazamox are applied [46]. The effect of imidazolinone group herbicides on increasing the purity of hybrid seeds when hybridized with Polima male sterile lines was not evaluated in this study.…”
Section: Improving Hybrid Seed Purity Using Imidazolinonesmentioning
confidence: 91%
“…At least seven male sterility systems have been used to produce rape hybrids, but they all have a number of drawbacks. These include the following: inheritance of male sterility systems is linked with unfavorable traits, it is time-consuming for cytoplasmic male sterility systems to establish isogenic pairs and other sterility systems can be unstable [46][47][48][49][50][51][52][53][54][55].…”
Section: Improving Hybrid Seed Purity Using Imidazolinonesmentioning
confidence: 99%
See 3 more Smart Citations